Validation study of the Malay version of the Myasthenia Gravis Quality of Life (MGQOL)15 and Myasthenia Gravis Activities of Daily Living (MGADL) questionnaires - Mohd Thabit, Alif Adlan; Rosli, Nor Azman; Solehan, Hana Maizuliana; Pilus, Zahariah; Mohammad Lotfie, Maskanah; Sahathevan, Ramesh; Mohamed Ibrahim, Norlinah; Hui, Jan Tan; Wan Yahya, Wan Nur Nafisah; Mahadzir, Hazlina; Md Rani, Shahrul Azmin; Zhe, Kang Law; et al. (ASEAN Neurological Association., 2016)
Myasthenia gravis (MG) is an immune mediated neuromuscular disease causing fatiguability, which can influence quality of life (QOL). MG disease status can be established with Myasthenia Gravis Quality of Life (MGQOL) 15 and Myasthenia Gravis Activities of Daily Living (MGADL) questionnaires to measure patients’ perception of MG-related dysfunction. This study aims to validate the translated Malay versions of the MGQOL15 and MGADL for use in Malay-speaking MG patients. By using the cross cultural adaptation process, both questionnaires were translated into Malay language. Two sets of MGQOL15 Malay version and MGADL Malay version were distributed to MG patients during their routine follow-up to be filled up one week apart. A total of 38 patients were recruited during this study comprising predominantly females compared to males (71% vs 29%) and Malays compared to non-Malays (60% vs 40%). The mean age was 52.5 years; with most of the patients in the 60-69 years old category (37%).The Spearman’s correlation coefficient was 0.987 for MGQOL-15 Malay version and 0.976 for MGADL Malay version, while the internal consistency for MGQOL15 Malay version was 0.952-0.957, and 0.677-0.694 for MGADL Malay version. The MGQOL15 Malay version and MGADL Malay version are reliable and valid instruments for the measurement of quality of life in MG patients in the local setting.